Effect of bumetanide on toluene diisocyanate induced contractions in guinea pig airways. Issue 1 (January 1993) - Mapp, C E; Boniotti, A; Papi, A; Maggi, C A; Di Stefano, A; Saetta, M; Ciaccia, A; Fabbri, L M
Abstract : BACKGROUND: The loop diuretic frusemide has been shown to inhibit the bronchoconstrictor response to exercise, inhaled allergen, distilled water, adenosine, and sodium metabisulphite. Toluene diisocyanate contracts smooth muscle by activating capsaicin sensitive nerves and causes asthma that shares many features with allergen induced asthma. METHODS: The study was designed to assess the effect of two loop diuretics, bumetanide (10 and 100 microM) and frusemide (100 microM), on smooth muscle contraction induced by toluene diisocyanate (0.03-1000 microM) in guinea pig airways with and, in the case of bumetanide, without epithelium. The effect of bumetanide on the response to acetylcholine, neurokinin A, and electrical field stimulation in guinea pig bronchial smooth muscle rings was also examined. RESULTS: Bumetanide (10 and 100 microM) had no effect on toluene diisocyanate induced contraction whether airway epithelium was present or not. Frusemide (100 microM) caused no significant inhibition of toluene diisocyanate induced contraction (mean reduction on the entire curve 25%). Bumetanide inhibited non-adrenergic, non-cholinergic contraction induced by electrical field stimulation of bronchi pretreated with atropine (1 microM) and indomethacin (5 microM) and this inhibition was inversely related to the frequency of stimulation, suggesting that bumetanide may be inhibiting transmitter release at the prejunctional level. Bumetanide and frusemide did not inhibit the responses to exogenous acetylcholine (0.1 microM) or neurokinin A (1 nM). CONCLUSIONS: Bumetanide and frusemide in doses that are known to inhibit non-adrenergic, non-cholinergic contraction due to electrical field stimulation failed to inhibit the response to toluene diisocyanate in guinea pig airways.